Analysis of bioactive components and pharmacokinetics of Caulophyllum robustum in rat plasma after oral administration by UPLC–ESI–MS/MS. Issue 3 (1st April 2021) - Duan, Ji-Xin; Li, Guo-Yu; Jian, Ji-Ping; Lü, Shao-Wa; Su, Hong; Xu, Dan; Guo, Yu-Yan; Kuang, Hai-Xue; Wang, Qiu-Hong
Abstract: A UPLC–MS/MS method was developed and validated the determination and pharmacokinetic study of magnoflorine, cauloside C, hederagenin, and oleanolic acid from Caulophyllum robustum . Digoxin was used as the internal standard. The pretreated plasma samples were carried out on a Waters ACQUITYUPLC HSS T3 column at 35 °C with a mobile phase of acetonitrile–water (90:10, v/v) at a flow rate of 0.2 mL/min. This article describes the most simple, sensitive, and validated UPLC–MS/MS method to date for the simultaneous successful determination of four compounds in rat plasma after oral administration of the extract of C. robustum and their pharmacokinetic studies. Graphical Abstract: